2019
DOI: 10.1038/s41368-018-0038-6
|View full text |Cite
|
Sign up to set email alerts
|

Enamel biomimetics—fiction or future of dentistry

Abstract: Tooth enamel is a complex mineralized tissue consisting of long and parallel apatite crystals configured into decussating enamel rods. In recent years, multiple approaches have been introduced to generate or regenerate this highly attractive biomaterial characterized by great mechanical strength paired with relative resilience and tissue compatibility. In the present review, we discuss five pathways toward enamel tissue engineering, (i) enamel synthesis using physico-chemical means, (ii) protein matrix-guided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
123
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(124 citation statements)
references
References 130 publications
(124 reference statements)
1
123
0
Order By: Relevance
“…The greater difference between test and control lesions, however, occurred in the impedance values compared with that in the morphometric measurements, thereby confirming that SAP P 11 -4 acts predominantly by regenerating the mineral structure of the enamel of the lesion body and not just the surface 23,24 . Moreover, at the last study visit at day 180, the impedance values for test lesions indicated regression of caries into very outer enamel, whereas the impedance values for the control lesions indicated still caries throughout the whole enamel layer 31,33 , which agrees with previous data that fluoride (in the present study as fluoride-based professional prophylaxis paste and home care toothpaste) only acts in the top 30-50 µm of the enamel surface 13,14,34 .…”
Section: Discussionsupporting
confidence: 92%
“…The greater difference between test and control lesions, however, occurred in the impedance values compared with that in the morphometric measurements, thereby confirming that SAP P 11 -4 acts predominantly by regenerating the mineral structure of the enamel of the lesion body and not just the surface 23,24 . Moreover, at the last study visit at day 180, the impedance values for test lesions indicated regression of caries into very outer enamel, whereas the impedance values for the control lesions indicated still caries throughout the whole enamel layer 31,33 , which agrees with previous data that fluoride (in the present study as fluoride-based professional prophylaxis paste and home care toothpaste) only acts in the top 30-50 µm of the enamel surface 13,14,34 .…”
Section: Discussionsupporting
confidence: 92%
“…Enamel, the hardest tissue in the human body, is a highly organized dental tissue, covering the outer layer of the tooth crown. It possesses unique mechanical and structural properties [29][30][31][32], relying on its high hydroxyapatite content, the arrangement of apatite crystals into enamel prisms, and finally, the alignment of these prisms in a picket-fence appearance in a tissue of high physical resilience and great hardness [33][34][35][36][37]. Ameloblasts, the enamel-forming cells, are specialized epithelial cells differentiating from the inner cells of the enamel organ [38].…”
Section: Enamel Regenerationmentioning
confidence: 99%
“…Finally, they undergo apoptosis and the mature enamel becomes acellular. As a result, once damaged, unlike other biomineralized hard tissues such as dentin and bone, the enamel cannot regenerate by itself [37,46]. Therefore, a reparative healing of destroyed enamel depends mainly, if at all, on acellular remineralization of superficial demineralized defects [47].…”
Section: Enamel Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, biomimetic in vitro strategies employing proteins which contribute to the EMP layer such as native amelogenin and leucine-rich amelogenin peptide (LRAP) have demonstrated the ability to bind hydroxyapatite crystals, which is crucial for remineralisation. The use of LRAP in vitro has demonstrated the de novo formation of HA [ 19 ]. This is of significant importance to researchers and dental clinicians to develop biomimetic peptides as potential treatments to initiate remineralisation.…”
Section: Introductionmentioning
confidence: 99%